2012
DOI: 10.1080/19648189.2012.668017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wetting-drying cycles on mortar samples affected by DEF

Abstract: International audienceThis article, which deals with the effect of wetting-drying (W-D) cycles on materials affected by delayed ettringite formation (DEF), has two main objectives. The first is to observe whether W-D cycles pre-damage samples, by using the replica technique. Scanning electron microscopy (SEM) observations of replicas show that W-D cycles lead to microcracks in the samples. The second objective of the study is to observe whether the cycles are necessary for development of DEF or if they only ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The results in Figure 3 show that the preliminary microcracking induced by the wetting-drying cycles significantly accelerates the appearance of expansion. This result is in accordance with those obtained by other researchers (Leklou, Aubert, & Escadeillas, 2012;Leklou et al, 2009;Pavoine, 2003;Petrov, 2003;Petrov & Tagnit-Hamou, 2004). The explanation for this acceleration may be the same as that for the effect of the W/C ratio: the microcracking induced by the wetting-drying cycles weakens the cement paste, on the one hand, and increases the ionic and hydrous transfers on the other.…”
Section: Effects Of the Wetting-drying Cyclessupporting
confidence: 93%
“…The results in Figure 3 show that the preliminary microcracking induced by the wetting-drying cycles significantly accelerates the appearance of expansion. This result is in accordance with those obtained by other researchers (Leklou, Aubert, & Escadeillas, 2012;Leklou et al, 2009;Pavoine, 2003;Petrov, 2003;Petrov & Tagnit-Hamou, 2004). The explanation for this acceleration may be the same as that for the effect of the W/C ratio: the microcracking induced by the wetting-drying cycles weakens the cement paste, on the one hand, and increases the ionic and hydrous transfers on the other.…”
Section: Effects Of the Wetting-drying Cyclessupporting
confidence: 93%
“…It has been well documented that wet/dry cycles with drying at 80°C will increase the rate of expansion caused by DEF (Leklou et al, 2012). Also, it has been found that heating cycles to 80°C with moisture will cause damage in concrete that would not have suffered from DEF (Fu & Beaudoin, 1996;Grabowski et al, 1992).…”
Section: Wetting and Drying Cyclesmentioning
confidence: 99%
“…Instead, the sulfate ions are adsorbed on the C-S-H phase at the elevated temperature (Collepardi, 2003). The exact temperature to which this occurs seems ambiguous, and some researchers report it as greater than 60°C/70°C (Bouzabata, Multon, Sellier, & Houari, 2012;Leklou, Aubert, & Escadeillas, 2012). It is generally agreed that curing temperatures above 70°C will cause DEF with typical cases; some researchers have found that the effects of DEF can be seen at lower temperatures, but this is usually associated with a special circumstance (Bouzabata et al, 2012;Taylor, Famy, & Scrivener, 2001).…”
Section: Delayed Ettringite Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…For Scanning Electron Microscopy (SEM) observations, a EVO40 (Carl Zeiss ) is used to perform the observations in the current contribution. The simple replica technique is firstly developed by Ollivier in [62] and followed by a series of papers [7,[63][64][65][66][67] for the visualization aspects devoted to the cement-based materials. The experimental observation findings using the simple replica method are shown in Table 4 and Figure 18, Figure 19, Figure 20 and Figure 21.…”
Section: Interface Between Aggregate and Cement Observation Via Repli...mentioning
confidence: 99%